Climate change impacts on plant diseases (SAARC Journal of Agriculture, 2017)
The change in Global climate is due to increasing concentration of greenhouse gases (GHG) in the atmosphere. The earths observed climatic changes over the past 50 years are primarily caused by various human activities. The increasing global temperature over the past century by about 0.8°C and expected to rise between 0.9 and 3.5°C by 2100. Such changes will not only have a great effect on the growth and cultivation of different crops but also affect the reproduction, spread and severity of many plant pathogens. Various plant disease models have been developed to incorporate more sophisticated climate predictions at various levels. At the level, the adaptive potential of plant and pathogen populations may prove to be one of the most important predictors of the magnitude of climate change effects. This review highlights various influences of climate change on plant diseases and their effects with suitable examples.SAARC J. Agri., 14(2): 200-209 (2016)